2018
DOI: 10.3233/jbr-180305
|View full text |Cite
|
Sign up to set email alerts
|

An immunological perspective for preventing cancer with berries

Abstract: Berries and their phytochemicals have well documented chemopreventive roles, but understanding their ability to regulate cancer immunology is only beginning to be explored. The literature, including human studies, suggests that berry components can modulate our immune system to delay cancer development. Moreover, their wide spectrum of phytochemicals suggests that they might influence the functions of multiple immune cells and different aspects of cancer immunity. Cancer immune-therapies are showing promise fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Epigenetic mechanisms regulate normal cellular functions and play a significant role in early developmental stages via linking the behavior of cells to their surrounding environment. However, alteration in epigenetic mechanisms leads to pathological consequences like cancer, neurological disorder, bone and skeletal diseases, and metabolic disorders (Lee, Chiou, Ho, & Pan et al, ). Epigenetic alterations in DNA mediated by DNA methylation, histones modifications, and miRNA regulation play important roles in cancer growth and progression.…”
Section: Epigenetic Regulation Of Cancer By Phytochemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic mechanisms regulate normal cellular functions and play a significant role in early developmental stages via linking the behavior of cells to their surrounding environment. However, alteration in epigenetic mechanisms leads to pathological consequences like cancer, neurological disorder, bone and skeletal diseases, and metabolic disorders (Lee, Chiou, Ho, & Pan et al, ). Epigenetic alterations in DNA mediated by DNA methylation, histones modifications, and miRNA regulation play important roles in cancer growth and progression.…”
Section: Epigenetic Regulation Of Cancer By Phytochemicalsmentioning
confidence: 99%
“…), black raspberry (Rubus occidentalis), blueberry (Vaccinium corymbosum), cranberry (Vaccinium macrocarpon), red raspberry (Rubus idaeus), and strawberry (Fragaria ananassa) are the good source of polyphenols and anthocyanins. Berries are widely consumed in our diet and have sought attention due to their potential benefits on human health (Miller, Feucht, & Schmid, 2019;Pan et al, 2018). Berries are being investigated for their potential chemopreventive effects as well as a protective role against various types of chronic diseases (Kristo, Klimis-Zacas, & Sikalidis, 2016;Stoner, 2009).…”
Section: Berrymentioning
confidence: 99%
“…We have shown that black raspberries (BRBs) and their anthocyanin and fiber fractions altered the composition and diversity of gut microbiota in F‐344 rats (Pan et al., 2017) and changed their metabolites in wild‐type C57BL/6 (Pan et al., 2017) and ApcMin/+ mice (Pan et al., 2015) as well as colorectal cancer patients (Pan et al., 2015). We further showed that those metabolites were responsible for BRBs’ anticancer effects by modulating host immunity (Pan et al., 2020; Pan et al., 2017; Pan et al., 2017; Pan et al., 2018; Pan et al., 2018; Pan et al., 2019; Pan et al., 2018; Pan et al., 2017).…”
Section: Introductionmentioning
confidence: 97%
“…In particular, berries such as blueberry, strawberry, raspberry and aronia have been reported to exert antioxidant activity, anti-cancer activity, anti-inflammatory activity and protective effect against cardiovascular diseases because the anthocyanin and phenolic compounds are richer in berries than in other fruits (Lee et al, 2015;Seeram, 2008). In addition, berries have been reported to contribute to the innate immunity and adaptive immune system of the human body through animal models and human studies (Govers et al, 2018;Pan et al, 2018). Therefore, as interest in healthy functional foods increases, intake of berry is increasing which is known to be beneficial for maintaining human health (An et al, 2015;Govers et al, 2018).…”
Section: Introductionmentioning
confidence: 99%